Determinan Diabetes Melitus Tipe 2 di Wilayah Puskesmas Alalak Selatan Kota Banjarmasin - Rusmini Yanti (Jurnal Skala Kesehatan, 2026)
South Kalimantan Province ranked 18th for diabetes mellitus cases in Indonesia in 2018. Banjarmasin City showed the highest prevalence, increasing from 1.7% in 2013 to 2.12% in 2018, with 16,013 cases recorded in 2022. Among the 27 community health centers, Alalak Selatan Health Center reported the highest coverage with 517 patients. This observational analytic study with a case-control design involved 52 cases and 52 controls selected through accidental sampling in three sub-districts under Alalak Selatan Health Center. The results revealed no significant association between age, gender, Body Mass Index (BMI), genetics, and knowledge with type 2 diabetes mellitus. However, diet and physical activity were significantly associated, with physical activity being the most influential factor. Improvement in dietary habits and increased physical activity, particularly exercise, are recommended for better diabetes mellitus prevention and management